Protection of distributed generation connected networks with coordination of overcurrent relays - Dewadasa, M.; Ghosh, Arindam; Ledwich, G. (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
The disconnection of distributed generators (DGs) from a distribution network for every abnormal condition drastically reduces the DG benefits and system reliability when DG penetration level is high. The DGs can be used to supply the load demand in the absence of grid supply if DGs are allowed to operate in islanded mode. In this paper, protection issues associated with disconnection of DGs are addressed in the context of a radial distribution feeder. Protection strategies are proposed to allow islanded operation and to restore the system performing auto-reclosing maintaining as many DG connections as possible. An overcurrent relay based protection scheme is proposed for a converter based DG connected radial feeder to operate either in grid-connected or islanded mode maximizing the DG benefits to customers. Moreover, an effective method is proposed to restore the system with DGs using auto-reclosers. The proposals are verified through PSCAD simulation and MATLAB calculations.